Pro-Kontra Normalisasi Hubungan Diplomatik Israel-Sudan - Muhammad Bachrul Ulum (Indonesia Center for Middle East Studies, 2021)
In 2020, four Arab countries normalized relations with Israel, namely the United Arab Emirates (UAE), Bahrain, Sudan and Morocco. Sudan has been known as a country carrying hard-line Pan-Islamism during the reign of Omar Al-Bashir, so the normalization of relations with Israel is very surprising. Aim of this study is explaining the reasons behind Sudan's agreement to the normalization offer from the US. This study uses a qualitative method with a historical approach to trace the normalization causes and utilizes the concept of